Beyond Green HRM: Understanding The Mediating and Moderating Factors in Sustainable Tourism Practices - Nugrahanti, Ratri Buda; Widiastuti, Tantri; Afandi, Donny Arif (CV ODIS, 2025)
This study systematically reviews the role of Green Human Resource Management (GHRM) in promoting environmental performance, employee engagement, and corporate sustainability within the tourism and hospitality industry. It examines key mediators, such as psychological green climate and responsible leadership, and explores moderating factors, including HRM system strength and leadership style, that influence GHRM effectiveness. The study also identifies challenges, research gaps, and future directions in GHRM adoption within hospitality organizations. Using a systematic literature review (SLR) methodology, this study follows the PRISMA framework to identify, screen, and analyze 38 peer-reviewed studies from Scopus (2015–2025). Articles were evaluated based on empirical rigor, relevance, and contributions to GHRM research in hospitality. The findings confirm that GHRM enhances environmental performance by fostering green employee behavior (GEB), affective commitment, and environmental awareness. Leadership engagement, HRM system strength, and employee personality traits moderate their effectiveness. However, financial constraints, regulatory inconsistencies, and cultural resistance pose adoption challenges. The study highlights the need for leadership-driven sustainability cultures and regulatory support to strengthen GHRM adoption. Finally, this study focuses on Scopus-indexed articles in tourism and hospitality, limiting its generalizability.